2011
DOI: 10.3727/096368910x564085
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Umbilical Cord Lining-Derived Epithelial Cells and Transplantation Potential

Abstract: In this study we describe the derivation and immunological characterization of a primary epithelial cell type from the human umbilical cord membrane. These cord lining epithelial cells (CLECs) expressed and/or secreted isoforms of the nonclassical human leukocyte antigen class I (HLA-1b) glycoproteins, HLA-G and E. Conditioned media from CLECs inhibited mitogen-stimulated T-lymphocyte responses, and in a mixed leukocyte reaction (MLR) assay, cocultured CLECs inhibited allogeneic responses with a concomitant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…In this study, we demonstrated that similar to human UCECs, 8 SUCECs also possess immunoregulatory properties. SUCECs significantly suppressed the proliferation of T cells in vitro in response to mitogen, suggesting that SUCECs will be valuable cell source to examine the role of these cells in a pig model of human inflammatory diseases.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In this study, we demonstrated that similar to human UCECs, 8 SUCECs also possess immunoregulatory properties. SUCECs significantly suppressed the proliferation of T cells in vitro in response to mitogen, suggesting that SUCECs will be valuable cell source to examine the role of these cells in a pig model of human inflammatory diseases.…”
Section: Discussionmentioning
confidence: 81%
“…Human UCECs have been isolated and characterized. 8,25,26 Similar to human UCECs, SUCECs were highly proliferative and expressed embryonic stem cell and pluripotency markers including SSEA-1, SSEA-4, TRA-1-60, TRA-1-81, and Oct-4 and showed in vitro differentiation potential. 25,26 The expression of these factors indicated that these cells possess many of the properties of embryonic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLECs were differentiated to be some type of epithelium by some invitro study [11], [12], [13]. Zhou Y, MacAry PA, et al, have shown many markers of corneal and limbal epithelial cells in CLECs and the safety of CLECs human transplantation [12], [14]. Reza HM, (2011) has differentiated CLECs to corneal epithelial cells and transplanted them to rabbit eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Together with insulin gene transfection in vitro , after peritoneal transplantation into sterptozotocin-induced diabetic mice, there was some improvement in glucose levels. [3] Our colleagues in Singapore[45] have used another model of autologous hepatocytes from streptozotocin-induced diabetic pigs. These separated hepatocytes were successfully transfected ex-vivo with a human insulin gene construct by electrophoration, and then the cells were injected directly back into the liver parenchyma using multiple separate injections.…”
mentioning
confidence: 99%